The funerary quipus of Cuspon as national cultural heritage - Zubieta Núñez, Filomeno (2018)
On April 27, 2017, the Ministry of Culture declared the ritual use of the quipus in the burial of the deceased in the village of Cuspón, province of Bolognesi (Ancash), as Cultural Heritage of the Nation. It was the corollary of 21 years of identification, study and valuation of this cultural expression. A first academic approach to the funeral quipus took place in 1996 and, over the years thereafter, they increased and matured, until - at the time - to manage before the Ministry of Culture its registration and safeguard. By Resolution No. 071-2017-MC, the ritual use of funerary quipus in Cuspón is now part of the Cultural Heritage of the Nation. With this landmark, the people of Cuspón reinforce their cultural and national identity.